2002
DOI: 10.1097/00024382-200212000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Exacerbates Burn Injury-Induced Host Responses in Rats

Abstract: Pathophysiology of burn injury with complications of gram-positive infections is not well characterized. We have developed an in vivo rat model to study the effects of burn injury along with intra-abdominal inoculation of Enterococcus faecalis. We hypothesized that although burn injury or E. faecalis inoculation by itself may not induce significant pathophysiological responses, the combination of the two can lead to adverse pathophysiological consequences. Sprague-Dawley rats were divided into 4 groups: group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Such priming of neutrophils with burn injury could be due to one or more of the known mediators generated during the course of burn injury. In our recent studies, we have documented that superimposition of E. faecalis infection on burn injury caused an eruption of host mortality not seen with either individual challenge (Goto et al ., ; Samonte et al ., ). We hypothesized that the Enterococcus bacteria, and/or factors related to these organisms, aggravate burn‐induced modulations in host defense by PMNs and thereby contribute to host morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such priming of neutrophils with burn injury could be due to one or more of the known mediators generated during the course of burn injury. In our recent studies, we have documented that superimposition of E. faecalis infection on burn injury caused an eruption of host mortality not seen with either individual challenge (Goto et al ., ; Samonte et al ., ). We hypothesized that the Enterococcus bacteria, and/or factors related to these organisms, aggravate burn‐induced modulations in host defense by PMNs and thereby contribute to host morbidity and mortality.…”
Section: Discussionmentioning
confidence: 98%
“…The results of our previous studies indicated a significant mortality in burn combined with E. faecalis infection (~60%). Burn or E. faecalis alone did not produce significant mortality (Goto et al ., ; Sayeed, ). The animals succumbed to death in B + EF group may have died from fulminant sepsis, bacterial translocation, or bacteremia; however, in this study we did not make any attempt to find the cause of death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, along with the slow initial BrdU incorporation shown here, could be related to hemodynamic changes resulting in the slowed postburn blood flow in the mesenteric vascular bed, which would restrict the transport of BrdU from the intraperitoneal cavity to the intestinal crypts by circulating blood (16,26). This effect may be compounded by increased postburn vascular permeability (21,26). The late appearance of BrdU immunopositive cells up to 18 hrs postinjection in burn rats could also be the result of slow delivery and/or clearance as a result of slow blood flow (16,21,26).…”
Section: Discussionmentioning
confidence: 93%
“…This effect may be compounded by increased postburn vascular permeability (21,26). The late appearance of BrdU immunopositive cells up to 18 hrs postinjection in burn rats could also be the result of slow delivery and/or clearance as a result of slow blood flow (16,21,26).…”
Section: Discussionmentioning
confidence: 99%